The Moderating Role Of Employee Engagement On The Influence Of Work Life Balance On Organizational Citizenship Behavior Through Burnout - Dwicahyani, Made Yurika Oka; Gorda, A.A.N. Oka Suryadinatha (Journal Research of Social Science, Economics, and Management, 2023)
Employees can experience developments that can advance the company, so companies must pay attention to the behavior of employees who work in the company. As many as 62% of millennial workers in Indonesia, they are considering and planning to leave their company. This is certainly not desired by companies where the millennial generation works. Based on field observations, researchers found that there is a problem of lack of employee OCB behavior. This is indicated by company turnover data for the last year. In this research, data will be collected based on quantitative methods. Questionnaires were distributed to 53 GlobalXtreme millennial generation employees using a saturated sampling technique. Partial Least Square (PLS) software will be used for the SEM analysis of this study model. According to the findings, OCB is significantly affected by work-life balance. Involvement has been shown to strengthen the connection between work-life balance and organisational citizenship behaviour. As burnout has a detrimental effect on organisational citizenship behaviour (OCB), work-life imbalance has the same effect. Work-life balance affects OCB via a mediating factor called burnout.